The role of IP3 receptors and SERCA pumps in restoring working memory under amyloid β induced Alzheimer's disease: a modeling study - Ziyi Huang; Lei Wang (Frontiers in Computational Neuroscience)
Memory impairment is a prevalent symptom in patients with Alzheimer's disease (AD), with working memory loss being the most prominent deficit. Recent experimental evidence suggests that abnormal calcium levels in the Endoplasmic Reticulum (ER) may disrupt synaptic transmission, leading to memory loss in AD patients. However, the specific mechanisms by which intracellular calcium homeostasis influences memory formation, storage, and recall in the context of AD remain unclear. In this study, we investigate the effects of intracellular calcium homeostasis on AD-related working memory (WM) using a spiking network model. We quantify memory storage by measuring the similarity between images during the training and testing phases. The model results indicate that ~90% of memory can be stored in the WM network under normal conditions. In contrast, the presence of amyloid beta (Aβ), associated with AD, significantly reduces this similarity, allowing only 54%-58% of memory to be stored, this alteration trend is consistent with previous experimental findings. Further analysis reveals that downregulating the activation of inositol triphosphate (IP3) receptors and upregulating the activation of the sarco-endoplasmic reticulum Ca2+ ATPase (SERCA) pumps can enhance memory performance, achieving about 78% and 77%, respectively. Moreover, simultaneously manipulating both IP3 and SERCA activations can increase memory capacity to around 81%. These findings suggest several potential therapeutic targets for addressing memory impairment in Aβ aggregation induced AD patients. Additionally, our network model could serve as a foundation for exploring further mechanisms that modulate memory dysfunction at the genetic, cellular, and network levels.